Border security - Phelps, James R. (Durham, North Carolina : Carolina Academic Press, LLC, 2024)
'Much has been written recently concerning the relationship between illegal immigration and border security (or the lack thereof). The concept of border security affects all of us, directly or indirectly. In the past, as we approached an international border physically, more people and communities were affected by illegal migration, drugs, and other criminal activities. This has changed considerably for all countries. Today, all across the world, whether in Denver, Chicago, London, Berlin, Rome, New York City, or Martha's Vineyard, the issues of uncontrolled migration and fentanyl, heroin, and other contraband is of paramount importance, making border security a major issue for all countries, states, and communities. Filled with relevant information, the authors' holistic approach provides a timely foundation for anyone interested in the topic. Descriptive and analytical, the text is designed to offer readers a balanced and up-to-date overview of what border security is, as well as the constant revisions to it that have occurred over the past 120 years. In the third edition of Border Security, authors Phelps, Dailey and Koenigsberg describe and discuss: Various definitions of'borders,' including geographical, political, and economic; What'border security' actually is, in relation to different types of borders and how the concept of a border developed historically; The classical concepts of border security, including the Walled City, Hadrian's Wall, the Maginot and Seigfried Lines, and the Great Walls of China; Border Patrol Operations, from 1904 to the present day; Present-day physical border security, including the various border fences and the impacts of illegal immigration; Maritime border security; The relationship between border security and transnational crime; Human trafficking; Transportation security as impacted by borders; How corruption in adjacent countries impacts border security; and Potential solutions to security along both the southern and northern borders of the United States'--
Puan Shaizimah Badzri/ Ketua Perpustakaan Undang-Undang/ shai@ukm.edu.my/ 0389216393/ OC/ Areesh Education & Trading
Includes bibliographical references and index.
Keywords: Border security -- United States; Smuggling -- Prevention -- United States; Human trafficking -- Prevention -- United States; United States -- Emigration and immigration -- Government policy